2012
DOI: 10.1016/j.rasd.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of context in the evaluation of reinforcer efficacy: Implications for the preference assessment outcomes

Abstract: Highly preferred stimuli were identified via two preference assessments (based on Fisher et al., 1992), the second of which included stimuli that were ranked low in the initial preference assessment. Following the preference assessments, a subset of stimuli was evaluated as reinforcers in single- and concurrent-operant arrangements. In general, stimuli that were identified as highly preferred in the initial preference assessment functioned as more effective reinforcers. These results are discussed in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…It should be noted that in their study they used the SMR protocol, which was not qEEG-guided and was applied similarly to every participant. Regarding feedback, stimulus used to work as reinforcer for some subjects might not work for others (Mangum et al, 2012). The NF is based on the application of the operant conditioning for the modulation of the EEG activity, so it is important that the feedback is a real reinforcer relevant for the individual patient (Fisher et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that in their study they used the SMR protocol, which was not qEEG-guided and was applied similarly to every participant. Regarding feedback, stimulus used to work as reinforcer for some subjects might not work for others (Mangum et al, 2012). The NF is based on the application of the operant conditioning for the modulation of the EEG activity, so it is important that the feedback is a real reinforcer relevant for the individual patient (Fisher et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Schabus et al (2017Schabus et al ( , 2014 and Hoedlmoser et al (2008) used the drawing of a sun along with a sound, whereas other studies did not specify what feedback was used (Cortoos et al, 2010;Hammer et al, 2011). We allowed the patient to choose both the form and the type of feedback in each session because, as previous studies have shown (Fisher et al, 1992;Mangum, Fredrick, Pabico, & Roane, 2012;Piazza, Fisher, Hagopian, Bowman, & Toole, 1996), rewards that are more relevant for the subject have a superior learning effect.…”
Section: Interventionmentioning
confidence: 99%
“…Assessments have taken place in school, home, and clinic/research settings (e.g., Fisher et al, 1992;Mangum, Roane, Fredrick, & Pabico, 2012;McCord, Iwata, Galensky, Ellingson, & Thomson, 2001). Most researchers indicated that the assessment took place in a space free from potential distractors (see for instance Fleming et al, 2010).…”
Section: Descriptive and Qualitative Analyses Of The Literaturementioning
confidence: 99%
“…To study the effects of context on preference, Mangum, Fredrick, Pabico, and Roane () conducted a paired‐stimulus preference assessment to identify a hierarchy of most‐to‐least preferred items and then assessed these items alone versus in pairs with a control condition during a reinforcer assessment. In Mangum et al's study, both high‐ and low‐preference items functioned as reinforcers with three children with developmental disabilities when presented alone in a COA.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, choice assessments can be an efficient method of identifying preferred stimuli that can be used as consequences to increase desired behavior. These assessments are effective at identifying reinforcers in the majority of cases (Mangum et al, ; Piazza et al, ).…”
Section: Introductionmentioning
confidence: 99%